Developments and challenges ahead in smart city frameworks - lessons from SmartSantander. (2015) - Mylonas, Georgios; Theodoridis, Evangelos
The domain of smart cities is currently burgeoning, with a lot of potential for scientific and socio-economic innovation gradually being revealed. It is also becoming apparent that cross-discipline research will be instrumental in designing and building smarter cities, where IoT technology is becoming omnipresent. SmartSantander is an FP7 project that built a massive city-scale IoT testbed aiming to provide both a tool for the research community and a functional system for the local government to implement operational city services. In this work, we present key smart cities projects, main application domains and representative smart city frameworks that reflect the latest advances in the smart cities domain and our own experience through SmartSantander. The project has deployed 51.910 IoT endpoints, offering a massive infrastructure to the community, as well as functional system services and a number of end-user applications. Based on these aspects, we identify and discuss a number of key scientific and technological challenges. We also present an overview of the developed system components and applications, and discuss the ways that current smart city challenges were handled in the project.